Disrupting ribulose-5-phosphate metabolic flux enhances riboflavin production in Escherichia coli BL21(DE3) - Junhui Ying; Jin Lu; Qiming Liu; Yingjie Pan; Xianfeng Bao; Junjun Yin; Bing Fu (PLoS ONE, 2025)
Riboflavin (vitamin B 2 ) is an essential water-soluble vitamin. To increase its production in a previously engineered strain, R203, we employed metabolic engineering strategies to improve the supply of ribulose-5-phosphate, a key precursor. Disruption of the genes pfkA and edd-eda , which are aimed at promoting ribulose-5-phosphate generation, increased riboflavin production by 51.27% and 65.81%, respectively. To minimize the consumption of ribulose-5-phosphate, we disrupted kdsD and gutQ , both of which encode D-arabinose 5-phosphate isomerase. Only the disruption of gutQ was effective, increasing production by 19.65%, whereas kdsD disruption had no significant effect. Furthermore, disrupting yajO and inserting the pgl gene increased production by 8.65% and 18.80%, respectively. In contrast, inserting ribM , which encodes a riboflavin transporter from Streptomyces davawensis , reduced production. The final engineered strain, R19, achieved a riboflavin titer of 2,546.35 ± 159.65 mg/L, representing a 287.35% increase over that of the starting strain. This study provides an effective strategy for high-level riboflavin production in recombinant Escherichia coli BL21(DE3) strains.